COMPOSITE MATERIALS IN DENTISTRY (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background: Composite materials are widely used in modern dentistry due to their favorable mechanical, biological, and aesthetic properties. Continuous improvements in material science have enhanced their clinical performance and durability.Objective: To review the classification of composite materials and evaluate the clinical significance of composites with light-resistant coatings.Methods: A literature-based analytical review was conducted using contemporary scientific publications and educational sources related to dental composite materials.Results: Composite materials are classified according to filler particle size, polymerization mechanism, and clinical application. Composites with light-resistant coatings demonstrate improved color stability, reduced surface degradation, and enhanced resistance to environmental factors.Conclusion: Composite materials with light-resistant coatings represent a significant advancement in dental materials, contributing to improved longevity and aesthetics of restorations.
Keywords: Composite materials, dental composites, classification, light-resistant coating, color stability.